The Effectiveness of the Qur’an Massive Program in Improving the Quality of TPQ Education to Develop a Qur’anic Generation in Kediri City - Islami , Yuliana Nurul (Academia Publication, 2024)
The purpose of this study was to evaluate the effectiveness of the Qur’an Massive Program in raising the standard of TPQ instruction in Kediri City and to identify the challenges that arose during its implementation. A descriptive qualitative study methodology using a literature review approach was utilized. The findings of the study showed that the program was effective in improving students’ Qur’anic literacy, enhancing the learning environment, and addressing several accessibility and sustainability-related issues. However, challenges remained, including the need for sustained support from the community and government, as well as ensuring consistency in the quality of teaching across various TPQs. By adopting best practices from other successful Qur’anic education programs, the Qur’an Massive Program had the potential to be more effective in achieving its goal of creating a generation that was morally upright and well-versed in Islamic teachings.